Synopsis of work-related indicator sets - Bundesverband der Betriebskrankenkassen, Essen; Kreis, Julia; Boedeker, Wolfgang (Essen, 2003)
"Based on the fact that several work-related health monitoring schemes already exist, the synopsis is aimed at compiling and evaluating these published or otherwise disseminated indicator sets. In terms of an inventory it shall provide an overview about what is available so far with regard to work-related health monitoring. Being aware of the fact that some compilations already exist (as, for example, the TNO report describes a number of monitoring schemes) we realised that, for our purposes, it was necessary to be more detailed at some points or approach the issue with a different focus. The purpose of our synopsis is to establish a sound basis for the future work within the project: For detecting gaps in existing health monitoring schemes it is on the one hand necessary to have a profound knowledge about the ongoing activities in this field – thus the required information will be provided by this document. Moreover, on the other hand, gaps can only be detected if there is an awareness of what might be needed beyond the already existing. Therefore a “model of work-related health monitoring from a public health perspective” shall be derived at the end of the synopsis." (From the introduction)